Inequalities of the Markov–Nikolskii type in regions with zero interior angles in Bergman space - Özkartepe, P. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5The order of growth of the module  of an arbitrary algebraic polynomial in a weighted Bergman space  $A_{p}(G,h),$  $p>0,$  is investigated in the regions with exterior nonzero and interior zero angles at finitely many points of the  boundary. We establish estimates of the Markov–,Nikolskii type for algebraic polynomials and clarify the behavior of derived polynomials at the points of zeros and poles of the weight function in bounded regions with piecewise-smooth boundary.